2013
DOI: 10.1016/j.jfda.2013.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of the medicinal herb Sanguisorba officinalis inhibit the entry of human immunodeficiency virus-1

Abstract: Highly active antiretroviral therapy (HAART) has been successful in reducing HIV-1-associated morbidity and mortality since its introduction in 1996. It, however, fails to eradicate HIV-1 infection thoroughly. The high cost of life-long HAART and the emergence of drug resistance among HIV-1-infected individuals have brought renewed pressure for the discovery of novel antivirals and alternative medicines. Traditional Chinese medicine (TCM) is one of the mainstreams of complementary and alternative medicine, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
1
23
0
1
Order By: Relevance
“…inhibiting the reverse transcriptase, protease, or integrase activities or interfering with virus entries into cells. In this regard, Sanguisorba officinalis and Pelargonium sidoides extracts inhibited the entry of the virus into the cells. Pometia pinnata and Mimusops elengi leaf extracts can modulate the activity of HIV integrase, and numerous vegetable extracts showed inhibitory potential on reverse transcriptase …”
Section: Introductionmentioning
confidence: 99%
“…inhibiting the reverse transcriptase, protease, or integrase activities or interfering with virus entries into cells. In this regard, Sanguisorba officinalis and Pelargonium sidoides extracts inhibited the entry of the virus into the cells. Pometia pinnata and Mimusops elengi leaf extracts can modulate the activity of HIV integrase, and numerous vegetable extracts showed inhibitory potential on reverse transcriptase …”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed that extracts form this plant have strong effect against avian E. coli [14]. The extracts are also considered as a new, natural anti-HIV-1 drug [4]. There was also confirmed that flavan-3-ols reduce the risk of cardiovascular disease and stroke [15].…”
Section: Ta B L Ementioning
confidence: 92%
“…In Poland it occurs mostly in southern regions, whereas in Mongolia it is spread through the whole country. The raw material collected from this plant are underground organs (rhizomes and roots) known for its healing properties [1][2][3][4]. They are used in the treatment of fever, bleeding, diarrhoea, haemorrhoids and burns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sanguisorba officinalis L. grows naturally in Korea, China, Japan, Siberia, and Europe. It possesses a variety of pharmacological properties including antioxidant , antitumor (Choi et al, 2012;Shin et al, 2012), antiangiogenic , and immunomodulatory effects (Cai et al, 2012;Liang et al, 2013). In addition, a variety of chemical constituents have been isolated from S. officinalis, and their biological properties have been evaluated (Tong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%